The effect of banking relationship on firm performance in Malaysian public listed companies - Putri Aidatul Sofina, Mohamad Jamil (2015)
Funds from banks play an important role in the growth and maintenance of a firm. Hence, it is important that a firm creates and maintains a good relationship with its bank in order to secure the funds. Establishing a good bank-firm relationship can also help to reduce conflicts between shareholders and creditors since close bank relationship helps the firm to get funding from other financial institutions. Relationships between a bank and a firm consist of two types: bank-borrower relationship and consumer-supplier relationship. The bank-borrower relationship involves primarily a loan agreement between two interested parties. Cooperation between a bank and a firm is more durable than customer-supplier relationships in terms of provision of financing. This thesis investigates the effect of banking relationships on firm performance on companies in Malaysian capital market. Seventy eight firms from the Top 100 public-listed companies in Bursa Malaysia are examined. Investigation is performed to show the effects of number of banking relationships, short-term financing, long-term financing, firm size, and foreign ownership on the firms’ performance as measured by return on assets (ROA), return on equity (ROE), and Tobin’s Q. Findings show a significant and negative relationships on the number of bank relationships for all of firm performance measures, consistent with previous studies. For ROA measurement, result shows a significant positive relationship with short-term financing, a finding also consistent with past studies. Short-term loan and long-term loan impact ROA and ROE positively, while affecting negatively firm performance measured by Tobin’s Q. ROA and ROE have a positive correlation with foreign ownership, while Tobin’s Q is negatively correlated with foreign ownership. In general, the study contributes to banking literature by investigating and evaluating the relationship of firm performance and lending banks in shareholders’ perspectives